Axis axis (Artiodactyla: Cervidae). (26th June 2021) - Randel, Charles J; Tomeček, John M
Abstract: Axis axis (Erxleben, 1777) is an Old World deer commonly known as chital, Indian spotted deer, or axis deer. It is one of five species in the genus Axis and is native to the Indian subcontinent, occurring in India, Nepal, Bhutan, Bangladesh, and Sri Lanka. Free-ranging and confined populations of A. axis have been established in Europe, Australia, and both North and South America. Globally, it is considered "Least Concern" (LC) by the International Union for Conservation of Nature and Natural Resources.